Analisis Mutu Pelayanan Pasien Rawat Inap Berdasarkan Metode Ipa (Importance, Performance Dan Analysis) Di Rumah Sakit Umum Daerah Sukoharjo - Setiawan, Agus, Sri Sugiarsi, SKM, M.Kes (2016)
Public expectations towards the fulfillment of the maximum degree of health and satisfying job in the hospital into its own for the hospital as health providers. This can be done by improving the quality of services in accordance with the requirements and standards of the profession. The purpose of this research is to know the factors that are considered important in influencing the perception of the customers against the quality of patient service in hospitals based on the method of IPA (Importance, Performance And Analysis). The population in this research is the were all patients class 3 as much as the 1201, with sampling as much of 60 respondents. How to use the method of purposive sampling sampling. The results showed that all the indicators of the Ministry from the table either in the category of perception and score in the category of quality of service expectations are important. Based on the analysis of using 5 dimensions of service quality dimensions that most are on A quadrant is a dimension of Reliability, most dimensions on quadrant B is the dimension of Reliability, most dimensions on quadrant C is the dimension of Responsiveness and emphaty, most dimensions are in quadrant D is the dimension of Tangible and Assurance. The conclusion of this research is the human factor received the most complaints, including speed, attitude and attention. Services that are not included in the category of low performance is the service of the hospital. The advice of this research is to increase the quality of human resources, training, increased knowledge and soft skills. Keywords : Service of quality, IPA(Importance, Performance And Analysis). Literature : 31, 1996 - 2014